Supply Chain Management And Performance At Case Study Company - Azmi, Amirul Asraf (Universiti Sains Malaysia, 2018)
The fast changing economic condition such as global competition and customer demands for high quality product and reduce lead time has a major impact on manufacturing industry. Supply Chain Management (SCM) is the integration and strategic alliance involving all the value-creating elements in the supply manufacturing, manufacturing and distribution from raw material extraction, the transformation process and end user consumption. As such, management are focusing on SCM to gain competitive advantage SCM is the one of the most important management practices for determining world class performance. The study explores the current SCM practices at a case study company. Data are collected from 25 respondents from the supply chain and logistic department in the company. It is found that the company adopt the SCOR model for their SCM. The performance of SCM from the customer perspective, financial perspective, learning and growth perspective and internal business perspective are also determined. These are used as the performance indicators of SCM. It is observed that the company did not give strong emphasize on financial issues in describing its performance. Overlooking this issues, may hinder the operational performance which may results in Supply Chain (SC) not being optimized. It is important for management from supply chain management to consider all these parameters when implementing supply chain practices in the supply chain. The relationships between supply chain management and supply chain performance are analysed using the Balanced Scorecard (BS) Method model. It is found that effective SCM will have an impact on SC Performance. A Balanced Scorecard tailored for the company is a put forward. This will help the company to recognize the issues and areas that need to be address.